Preservation, handling and care of the dental prosthesis in patients assisted in a comprehensive general stomatology service - Josefa Navarro Nápoles; Tania Rodríguez Carbonell; Marcia Hortensia Corona Carpio; Zulema Áreas Arañó; Luisa Limonta Bandera (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and cross-sectional study of the 110 patients with dental prosthesis assisted in the General comprehensive stomatology service of "Martires del Moncada" Teaching Provincial Stomatological Clinic in Santiago de Cuba, was carried out from September to December, 2015, aimed at identifying the preservation, caring and handling in the prosthetic appliances.  There was a prevalence of the patients that carried upper total prosthesis (50.0%), of those that had used them for more than 5 years (52.7%) and of the prosthesis in poor conditions (58.2%); poor oral hygiene was more frequent in the male sex (67.7%) when implementing the Love index.